KAJIAN SOSIAL DAN EKONOMI NELAYAN PUKAT CINCIN DI PANGKALAN PENDARATAN IKAN PEUDADA, KABUPATEN BIREUN - Ratna Mutia Aprilla; Salsabila Putri Ardha; Junaidi M. Affan; Imelda Agustina; Nanda Rizki Purnama (Universitas Pattimura, 2025)
This study aims to examine the social and economic conditions of purse seine fishermen at the Fish Landing Base Peudada, Bireuen Regency. The data collection methods used include observation and interviews, employing the Accidental Sampling technique with 40 active fishermen. The data gathered consists of primary data obtained through direct interviews and secondary data from relevant literature. The results of the study show that the purse seine fishermen at Fish Landing Base Peudada have an annual net income of approximately IDR 759,762,000, with a monthly income of around IDR 63,313,500. However, their income per fishing trip is only about IDR 6,331,350, and when divided equally, each fisherman receives approximately IDR 316,568 per trip. Although the monthly income is close to the provincial minimum wage, the average household expenses of the fishermen amount to IDR 3,685,000, indicating that they are still economically insecure. From a social perspective, the study reveals that the majority of the fishermen are aged between 36-45 years, with 53% of them having completed only junior high school. Additionally, 75% of the fishermen live in permanent houses. The longest fishing experience is more than 20 years for 30% of the fishermen. The study finds that the economic conditions of the fishermen are far from prosperous, influenced by high household expenses and the instability of their participation in every fishing trip.